2015
DOI: 10.1186/s12865-015-0138-4
|View full text |Cite
|
Sign up to set email alerts
|

Th17 cells reflect colon submucosal pathologic changes in active eosinophilic granulomatosis with polyangiitis

Abstract: BackgroundChronic eosinophilic pneumonia (CEP) or eosinophilic gastroenteritis (EG), or both, with asthma precede the onset of eosinophilic granulomatosis with polyangiitis (EGPA) in half of all EGPA patients. It is not known what determines whether patients with CEP or with EG following asthma will develop EGPA.MethodsWe studied 17 EGPA patients and 12 patients with CEP but without EGPA. We assayed serum ICAM-1, VCAM-1, and VEGF, and the percentage of peripheral blood CD4+ T cells producing IL-17 (Th17 cells)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
0
17
0
1
Order By: Relevance
“…Previously, we reported that the number of inducible T reg cells (CD4 + T cells producing IL-10) in peripheral blood was comparable in patients with active CEP or EGPA at onset 6 and that the number of T helper 17 cells (CD4 + T cells producing IL-17) was comparable in patients with active or inactive CEP or EGPA at onset or relapse. 43 We have also reported that the percentage of CD4 + CD25 + T cells (T reg cells) was correlated with the number of inducible T reg cells (IL-10-producing cells) or naturally occurring T reg cells (FOXP3 + CD4 + ) in patients with EGPA. 51 In addition, we have reported that the percentage of CD83 + dendritic cells, which are mature dendritic cells, was significantly correlated with the number of naturally occurring or inducible T reg cells (CD4 + CD25 + T cells producing IL-10) or the number of TGF-β cells, but not the number of eosinophils in patients with EGPA.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Previously, we reported that the number of inducible T reg cells (CD4 + T cells producing IL-10) in peripheral blood was comparable in patients with active CEP or EGPA at onset 6 and that the number of T helper 17 cells (CD4 + T cells producing IL-17) was comparable in patients with active or inactive CEP or EGPA at onset or relapse. 43 We have also reported that the percentage of CD4 + CD25 + T cells (T reg cells) was correlated with the number of inducible T reg cells (IL-10-producing cells) or naturally occurring T reg cells (FOXP3 + CD4 + ) in patients with EGPA. 51 In addition, we have reported that the percentage of CD83 + dendritic cells, which are mature dendritic cells, was significantly correlated with the number of naturally occurring or inducible T reg cells (CD4 + CD25 + T cells producing IL-10) or the number of TGF-β cells, but not the number of eosinophils in patients with EGPA.…”
Section: Discussionmentioning
confidence: 92%
“…7 Previously, we reported a higher serum vascular cell adhesion protein 1 concentration and lower serum vascular endothelial growth factor concentration in patients with EGPA at onset. 43 We hypothesized that angiogenesis and vascular permeability is promoted by endothelial cells activated by IL-33. 22 We also hypothesize that serum IL-33 concentration might be reflected in the disease activity or severity of EGPA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 In addition, IL-17 enhances eosinophilic recruitment during airway inflammation in allergic asthma. 11,12 Hence, there might be clinical benefit by inhibiting IL-17 immunity.…”
Section: Introductionmentioning
confidence: 99%
“…A szöveti károsodásban fontos szerepet játszik a kóros ANCA jelenléte és a következményes neutrophil aktiváció (8). Az újabb irodalmi adatok a fokozott IL-17A termelődésre is felhívják a figyelmet, ami a granuloma képződésében szerepet játszhat (9).…”
Section: Megbeszélésunclassified